2019
DOI: 10.1002/ecs2.2780
|View full text |Cite
|
Sign up to set email alerts
|

Soil characteristics are associated with gradients of big sagebrush canopy structure after disturbance

Abstract: Reestablishing shrub canopy cover after disturbance in semi‐arid ecosystems, such as sagebrush steppe, is essential to provide wildlife habitat and restore ecosystem functioning. While several studies have explored the effects of landscape and climate factors on the success or failure of sagebrush seeding, the influence of soil properties on gradients of shrub canopy structure in successfully seeded areas remains largely unexplored. In this study, we evaluated associations between soil properties and gradients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 40 publications
(82 reference statements)
2
15
1
Order By: Relevance
“…Topography and potential incident solar radiation modify soil temperature and water availability and influence fuel loads (e.g., exotic annual grass abundance) at landscape and community scales (Brooks et al., 2016; Williamson et al., 2020). Edaphic factors are known to strongly influence the structure and function of vegetation in sagebrush ecosystems, where soil surface and profile characteristics can affect canopy growth and morphology via moisture and nutrient availability (Barnard et al., 2019; Nelson et al., 2014). Post‐fire succession has also been generally linked to soil moisture availability, vegetation communities, physiography, and soil‐surface conditions (Barker et al., 2019; Condon & Pyke, 2018; Germino et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Topography and potential incident solar radiation modify soil temperature and water availability and influence fuel loads (e.g., exotic annual grass abundance) at landscape and community scales (Brooks et al., 2016; Williamson et al., 2020). Edaphic factors are known to strongly influence the structure and function of vegetation in sagebrush ecosystems, where soil surface and profile characteristics can affect canopy growth and morphology via moisture and nutrient availability (Barnard et al., 2019; Nelson et al., 2014). Post‐fire succession has also been generally linked to soil moisture availability, vegetation communities, physiography, and soil‐surface conditions (Barker et al., 2019; Condon & Pyke, 2018; Germino et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…We determined mean elevation of each well pad using a 1/3 arc‐second DEM (U.S. Geological Survey, 2017) with hydrological corrections from Optimized Pit Removal software (Soille, 2004). Soil characteristics may influence growth and survival of sagebrush, including soil texture, soil depth, and salinity, among other factors (Barnard et al, 2019; Germino & Reinhardt, 2014; Renne et al, 2019). We therefore used a recent soil properties dataset (Nauman & Duniway, 2020) to represent several important soil variables.…”
Section: Methodsmentioning
confidence: 99%
“…Second, parameters from studies that explicitly model variation in sagebrush recovery processes as a function of underlying R&R can better inform predictions from statetransition models (e.g., Briske et al, 2008;Stringham et al, 2016;Chambers et al, 2017) and subsequent sage-grouse response. Similar to the studies described above, additional meta-analyses of space for time studies describing sagebrush recovery processes (e.g., Knutson et al, 2014;Barnard et al, 2019) following restoration (Pilliod and Welty, 2013;Pilliod et al, 2017b) in the context of spatially explicit R&R layers at coarse to fine scales (e.g., soil moisture and temperature sub-classes) would be especially useful; as would back-in-time approaches (Shi et al, 2017) that leverage extensive time series of archived satellite data (e.g., Landsat) across expansive extents to classify changes in land cover at relatively high resolution (e.g., percentages of functional plant types with 900 m 2 pixels) (Xian et al, 2015) and then relate back to R&R in a similar fashion. For the latter case, Monroe et al (2020) recently utilized a back-intime approach to quantify factors influencing sagebrush recovery on reclaimed well-pads in Wyoming, and found that dynamic variables such as annual precipitation and temperature modified annual rates of change in cover (e.g., engineering resilience) based on more static state-variables such as soil type and topographic position describing general resilience.…”
Section: Improving Estimates Of Sagebrush Engineering and Spatial Resmentioning
confidence: 98%
“…The aforementioned studies contribute to a proliferation of research that explicitly incorporate general R&R into planning and prioritization at the local-scale within the context (implicitly or explicitly) of sage-grouse habitat requirements and distribution at mid-scales (e.g., Knutson et al, 2014;Pyke et al, 2015;Chambers et al, 2017Chambers et al, , 2019bBarnard et al, 2019). However, few have modeled specifically quantified changes in sage-grouse habitat selection post-restoration as a function of predicted land cover responses to underlying general resilience.…”
Section: Scaling-down Mid-scale Models To Better Inform Local Site Sementioning
confidence: 99%